IBN SINA'S PHILOSOPHICAL THOUGHT: CONTRIBUTIONS AND INFLUENCES IN ISLAMIC PHILOSOPHY - Muhammad Alfian Tuflih; Rusiadi (Adisam Publisher, 2025)
The philosophical thought of Ibn Sina (Avicenna) contributed greatly to the development of Islamic philosophy by integrating various disciplines such as metaphysics, logic, psychology, and medicine into a systematic framework. His concepts such as “Wujud Wajib” explain the existence of God as an absolute entity, providing an important basis for subsequent philosophers. His influence can be seen in the scientific method that prioritizes reason and empirical observation. Ibn Sina's intellectual legacy connected the Greek tradition of thought with Islamic teachings, had a broad impact on the development of philosophy in both the Islamic world and medieval Europe, and became an important reference for subsequent generations in the pursuit of harmony between science and spirituality.